Probing relaxation dynamics of a few strongly correlated bosons in a 1D triple well optical lattice. (15th October 2019) - Bera, S; Roy, R; Gammal, A; Chakrabarti, B; Chatterjee, B
Abstract: The relaxation process of a few strongly interacting bosons in a triple well optical lattice is studied from the first principle using the multiconfigurational time-dependent Hartree method for bosons. We report the contrasting response of the system under two independent quench processes: an interaction quench and a lattice depth quench. We analyze the evolution of the reduced one-body density matrix, two-body density and the Shannon information entropy for a wide range of lattice depth and interaction strength parameters. For the strong interaction quench, we observe a very fast relaxation to the steady state. In contrast, for the lattice depth quench, we observe collapse–revival dynamics in all the key measures. We also provide the best fitting formulas for relaxation and revival time which follow power law decay.